Integration of IMTAQ and Science and Technology in Improving Community Empowerment in Ulujami Village, South Jakarta - Sofwan Manaf; Ahmad Syaifullah; Much. Hasan Darojat (Universitas Darunnajah, Jakarta, Indonesia, 2023)
Abstract The situation of the metropolitan community which tends to be busy and hedonistic causes the emergence of social phenomena in the community, this case occurs among the people in Ulujami Village. The social phenomenon that occurs causes low public concern for participation in social, religious activities and awareness of the importance of mastering technology for owners of micro, small and medium enterprises. Based on these problems, Darunnajah University students created a community service program by carrying out community empowerment activities in an effort to improve IMTAQ and science and technology and the integration of the two in Ulujami Village. Because by integrating IMTAQ and science and technology in life, it can form a rabbani society and intellect. To realize these activities, various activities are carried out by actively involving the community. The activity focuses on improving the community's ability to study religion and technology by holding socialization activities to village officials and communities in an inclusive manner, conducting socialization and training to the younger generation and teaching religion to children as the basis for their education. Meanwhile, the implementation of technology empowerment is carried out for MSME owners to be able to develop their business through marketing with social media and online.